Preparation method and application of double-quencher Au-coated NiFeMOFs composite material
By preparing Au@NiFeMOFs composite material in situ reduction on the NiFeMOF surface, an electrochemiluminescent biosensor with high sensitivity and stability was constructed, which solved the problem of low detection efficiency of Vibrio parahaemolyticus and achieved rapid and portable detection capabilities.
Patent Information
- Application Number
- CN202411049521.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-01
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art cannot meet the needs of rapid, sensitive and efficient detection of Vibrio parahaemolyticus. The traditional isolation and culture method is inefficient and lacks portability and on-site detection capabilities.
The double quencher Au@NiFeMOFs composite was prepared by a green method. The gold nanoparticles were uniformly loaded on the NiFeMOF surface by in-situ reduction, forming a porous structure to improve conductivity and electrocatalytic activity, and used to construct an electrochemiluminescent biosensor.
It has achieved an electrochemiluminescent biosensor with high sensitivity and good stability, which can quickly and portably detect the V. parahaemolyticus TLH gene, which is low in cost and easy to obtain raw materials, and is suitable for large-scale production.
Smart Images

Figure CN119186640A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of novel functional materials and biosensor technology, and in particular to a preparation method and application of a double quencher Au@NiFeMOFs composite material. Background Art
[0002] There are many marine pathogens in natural seawater. The presence of these pathogens is not only related to the development of aquaculture, but also poses a huge hidden danger to human health. As a marine pathogen, Vibrio parahaemolyticus is widely present in seawater and various seafood products. The phenomenon of food poisoning caused by it in my country and around the world has increased year by year, and it has become one of the most serious marine pathogens. Common detection genes of Vibrio parahaemolyticus include TLH, TDH, and TRH genes. The TLH gene in Vibrio parahaemolyticus is a hemolysin gene that is not related to human diseases. Previous studies have shown that this hemolysin gene exists in all Vibrio parahaemolyticus strains, so it is considered to be a specific target for detecting Vibrio parahaemolyticus.
[0003] At present, the national standard detection method for Vibrio parahaemolyticus is the traditional isolation and culture method, which cannot meet the current requirements for rapid, sensitive and efficient detection. Therefore, in recent years, a series of new detection methods have gradually entered our field of vision. These include polymerase chain reaction, loop-mediated isothermal amplification technology, enzyme-linked immunosorbent assay, and biosensors. Biosensors have the advantages of fast detection speed, low cost, simple operation, and can be used for on-site detection at any time, which has attracted much attention. Electrochemiluminescence biosensors not only have low background signals, good stability, fast response, high sensitivity, and simplicity, but are also portable and can achieve on-site real-time detection. They currently have great development prospects.
[0004] Gold nanoparticles also have excellent electrochemical properties and synergistic effects. Loading metal / metal oxide nanoparticles into MOF to prepare composite materials is a very attractive field. The MOF metal organic framework provides metal / metal oxide nanoparticles with adjustable pore size and larger specific surface area, prevents particle aggregation, and provides them with more functional active sites. When metal / metal oxide nanoparticles have better dispersibility in the environment, they may show better performance. On the other hand, metal / metal oxide nanoparticles can improve the conductivity, electrocatalytic activity and electrochemical activity of the heterogeneous framework structure of MOF. Therefore, the electrochemiluminescent biosensor prepared from the composite material of metal / metal oxide nanoparticles and MOF shows excellent stability, good reproducibility and higher sensitivity. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a preparation method and application of a dual quencher Au@NiFeMOFs composite material. The present invention uses readily available nickel sources and iron sources to obtain a precipitated bimetallic NiFeMOF material by a green method of stirring at room temperature; after drying the above material, gold nanoparticles are compounded with NiFeMOF by a surface growth method to obtain an Au@NiFeMOF composite material. The porous structure and high specific surface area of the NiFeMOF prepared by the present invention can prevent the aggregation of gold nanoparticles and increase more active sites, while the gold nanoparticles can improve the conductivity and electrocatalytic activity of the framework structure, so that the Au@NiFeMOF composite material exhibits excellent electrochemical properties.
[0006] To achieve the above purpose, the technical solution designed by the present invention is as follows:
[0007] The invention provides a method for preparing an Au@NiFeMOF composite material. The method uses NiFeMOF as a carrier and uniformly loads gold nanoparticles on the surface of NiFeMOF by a surface in-situ reduction method to synthesize the Au@NiFeMOF composite material.
[0008] Furthermore, the preparation method of the NiFeMOF is as follows:
[0009] a. Weigh potassium ferrocyanide, nickel chloride hexahydrate and sodium citrate;
[0010] b. dissolving potassium ferrocyanide in water to obtain a potassium ferrocyanide solution;
[0011] c. Then dissolving nickel chloride hexahydrate and sodium citrate in water to obtain a nickel source mixture;
[0012] d. The potassium ferrocyanide solution and the nickel source mixed solution are mixed and dissolved by ultrasonication, and stirred until the solution becomes turbid and produces a large amount of precipitate, which is then washed and dried to obtain NiFeMOF.
[0013] Furthermore, the mass ratio of potassium ferrocyanide, nickel chloride hexahydrate and sodium citrate is 1:1-1.2:2-2.2.
[0014] Furthermore, the mass ratio of potassium ferrocyanide, nickel chloride hexahydrate and sodium citrate is 1:1.09:2.03.
[0015] Furthermore, the Au@NiFeMOF composite material is loaded by the following method:
[0016] a. Weigh NiFeMOF, polyvinyl pyrrolidone, potassium carbonate and sodium borohydride to prepare a 1% HAuCl4 solution;
[0017] b. dissolving NiFeMOF and potassium carbonate in water to obtain NiFeMOF solution and potassium carbonate solution respectively;
[0018] c. Add HAuCl4 solution to the NiFeMOF solution, stir evenly, then add polyvinyl pyrrolidone (abbreviated as PVP to prevent aggregation of gold nanoparticles); then add potassium carbonate solution, and finally add sodium borohydride and stir evenly, centrifuge, wash and dry to obtain Au@NiFeMOF composite material.
[0019] Furthermore, the mass ratio of NiFeMOF, polyvinyl pyrrolidone, potassium carbonate and sodium borohydride is 1:0.8-1.2:1-1.5:1.7-2.5; the mass volume ratio of NiFeMOF to HAuCl4 solution is 7.5-9 mg / mL.
[0020] Furthermore, the mass ratio of NiFeMOF, polyvinyl pyrrolidone, potassium carbonate and sodium borohydride is 1:1:1.4:2.25; the mass volume ratio of NiFeMOF to HAuCl4 solution is 8.3 mg / mL.
[0021] The present invention also provides an application of the Au@NiFeMOF composite material in constructing an electrochemiluminescent biosensor.
[0022] The present invention also provides a method for constructing an electrochemiluminescent biosensor based on the Au@NiFeMOFs composite material, comprising the following steps:
[0023] a. dissolving Au@NiFeMOF in N,N-dimethylformamide (DMF) to obtain Au@NiFeMOF solution;
[0024] b. polishing the glassy carbon electrode, then cleaning it with deionized water, anhydrous ethanol and deionized water in turn, blowing the surface dry with N2, pre-treating and drying it for later use, and obtaining a pre-treated glassy carbon electrode;
[0025] c. Drop 5 μL of fluorescent molybdenum disulfide (MoS2QDs) quantum dot luminescent material on the surface of the pretreated glassy carbon electrode, dry it, then continue to drop 2 μL of 1-ethyl-(3-dimethylaminopropyl) carbodiimide (EDC) and 2 μL of N-hydroxysuccinimide (NHS) solution on the glassy carbon electrode, add 4 μL of hairpin DNA after drying, then add 2 μL of tri(2-carboxyethyl)phosphine (TCEP), and then drop 4 μL of Au@NiFeMOF solution, add 5 μL of bovine serum albumin (BSA) solution after drying, and finally dry it to obtain the modified electrode;
[0026] d. A three-electrode system was used, with the prepared modified electrode as the working electrode, the platinum electrode as the auxiliary electrode, and the silver-silver chloride electrode as the reference electrode. The above three electrodes were inserted into a PBS buffer solution containing a co-reactant. The electrochemiluminescence signal was tested using a BPCL ultra-weak luminescence instrument, and the intensity of the electrochemiluminescence signal was recorded. Finally, an electrochemical biosensor based on Au@NiFeMOFs composite material was constructed.
[0027] Furthermore, in step c), the base sequence of the hairpin DNA and the groups modified at both ends are as follows:
[0028] NH2-(CH2)6-GGAAGACGTGAACGCAAGTGATCCTTTCTTC C-(CH2)6-SH.
[0029] The present invention also provides an application of the electrochemiluminescent biosensor prepared by the above method in detecting the TLH gene of Vibrio parahaemolyticus, comprising the following steps:
[0030] a. Dilute the 10 μM TLH gene DNA solution using PBS buffer solution to obtain a 100 pM to 10 aM DNA solution; wherein the base sequence of the TLH gene is as follows:
[0031] GGTTGATGTCCAAACAAGGATCACTTGCGTTCACGAAACCGGTGCTCTTCT;
[0032] b. Then the DNA solution is added dropwise to the modified electrode surface of the electrochemiluminescent biosensor and dried for testing; the concentration of the Vibrio parahaemolyticus TLH gene is detected.
[0033] Beneficial effects of the present invention:
[0034] The Au@NiFeMOF composite material prepared by the present invention has gold nanoparticles interacting with NiFeMOF, and the gold nanoparticles improve the conductivity, electrocatalytic activity and electrochemical activity of the heterogeneous framework structure of NiFeMOF; while NiFeMOF increases the adjustable pore size and larger specific surface area for the gold nanoparticles, prevents particle aggregation, and provides more functional active sites for them; the interaction between the two makes Au@NiFeMOF show excellent performance in the application of electrochemical biosensors. When the ECL double quencher prepared by the present invention is used as the energy acceptor, the efficiency of electrochemiluminescence resonance energy transfer (ECL-RET) is higher, and the prepared electrochemical biosensor has higher sensitivity and better stability. The preparation method provided by the present invention has a simple process, easy to obtain raw materials, low cost and can be mass-produced, and the prepared composite material has the characteristics of consistent morphology, stable performance, excellent electrochemical performance, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is the transmission electron microscope (TEM) image of NiMOF;
[0036] Figure 2 is the scanning electron microscope (SEM) image of Au@NiFeMOF composite material;
[0037] Figure 3 This is the scanning electron microscope energy spectrum (EDS) image of Au@NiFeMOF composite material;
[0038] Figure 4 X-ray diffraction analysis (XRD) diagram of NiFeMOF and Au@NiFeMOF composite materials;
[0039] Figure 5 Fourier infrared spectra of NiFeMOF and Au@NiFeMOF composites;
[0040] Figure 6 Ultraviolet-visible absorption spectra (UV) of NiFeMOF and Au@NiFeMOF composite materials;
[0041] Figure 7 Cyclic voltammetry (CV) diagram of the sensor preparation process based on Au@NiFeMOF composite material;
[0042] Figure 8 The electrochemical impedance spectroscopy (EIS) graph of the sensor preparation process based on Au@NiFeMOF composite material;
[0043] Fig. 9 This is the relationship diagram between the linear test target DNA concentration and electrochemiluminescence intensity based on the Au@NiFeMOF composite material sensor;
[0044] Fig.10 The linear fitting diagram of the target DNA concentration and electrochemiluminescence intensity detected by the Au@NiFeMOF composite sensor;
[0045] Fig.11 Diagram of the preparation process of Au@NiFeMOF composite material sensor. DETAILED DESCRIPTION
[0046] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand.
[0047] Example 1
[0048] Preparation method of ECL dual quencher Au@NiFeMOFs composite material:
[0049] (1) Preparation of NiFeMOF:
[0050] a. Weigh 65 mg potassium ferrocyanide, 71 mg nickel chloride hexahydrate and 132 mg sodium citrate;
[0051] b. dissolving potassium ferrocyanide in water to obtain a potassium ferrocyanide solution;
[0052] c. Then dissolving nickel chloride hexahydrate and sodium citrate in water to obtain a nickel source mixture;
[0053] d. The potassium ferrocyanide solution and the nickel source mixed solution are mixed and dissolved by ultrasonication, and stirred until the solution becomes turbid and produces a large amount of precipitate, which is then washed and dried to obtain NiFeMOF.
[0054] (2) Preparation of Au@NiFeMOFs composite materials:
[0055] a. Weigh 20 mg NiFeMOF, 20 mg PVP, 28 mg potassium carbonate and 45 mg sodium borohydride, and prepare 3 mL of 1% HAuCl4 solution.
[0056] b. Dissolve NiFeMOF and potassium carbonate in water to obtain NiFeMOF solution and potassium carbonate solution respectively.
[0057] c. Add HAuCl4 solution to the NiFeMOF solution, stir for 5 minutes, then add PVP to prevent aggregation of gold nanoparticles; then add potassium carbonate solution, and finally add sodium borohydride as a reducing agent, stir for 1 hour, centrifuge, wash and dry to obtain a cubic Au@NiFeMOF composite material.
[0058] like Figures 1 to 6 It can be seen that the morphology of the NiFeMOF bimetallic material is a cube with uniform morphology and a smooth surface. The size of the NiFeMOF material is about 150nm, and the size is relatively uniform.
[0059] Depend on Figure 2 It can be seen that AuNPs grew on the surface of NiFeMOF to form Au@NiFeMOF composite materials, and the surface of the composite materials became rough;
[0060] Depend on Figure 3 It can be seen that the three elements of Au, Ni and Fe are evenly distributed in the elements of the entire composite material, and the content of Au element is relatively small;
[0061] Depend on Figure 4It can be seen that the crystal structure of NiFeMOF was preliminarily observed by X-ray diffraction, and the characteristic diffraction peaks of the face-centered cubic structure (JCPDS card 43-0772) appeared, and when gold nanoparticles were grown in situ on the surface of NiFeMOF, the crystallinity did not change, and the structure did not change;
[0062] Depend on Figure 5 It can be seen that NiFeMOF has a -1 and 1615cm -1 The peak at 2167cm corresponds to the stretching and bending vibrations of OH, while the peak at 2167cm -1 and 2095cm -1 The peak corresponds to the characteristic stretching vibration of CN;
[0063] Depend on Figure 6 It can be seen that NiFe and Au@NiFeMOF have obvious characteristic peaks at 435 and 446 nm, respectively;
[0064] In summary, Au@NiFeMOF composite materials showed characteristic peaks at multiple crystal planes such as 200, 220, 400, and 420, proving that the material was successfully synthesized. In addition, no shift was found in the positions of the characteristic peaks of NiFeMOF and Au@NiFeMOF, proving that gold nanoparticles grew on the surface of NiFeMOF, and the crystallinity and structure did not change before and after the composite.
[0065] Example 2
[0066] Construction of electrochemical biosensor based on Au@NiFeMOFs composites:
[0067] a. Dissolve Au@NiFeMOF in DMF to obtain Au@NiFeMOF solution.
[0068] b. Polish the glassy carbon electrode, then clean it with deionized water, anhydrous ethanol, and deionized water in turn, blow dry the surface with N2, and pre-treat and dry it for use.
[0069] c. Drop 5 μL of MoS2QDs quantum dot luminescent material on the surface of the pretreated glassy carbon electrode, dry it under a xenon lamp for 20 min, then continue to drop 2 μL of 4 mg / mL EDC and 4 mg / mL NHS solution on the electrode, dry it under a xenon lamp for 10 min, then add 4 μL of hairpin DNA, where the base sequence of the hairpin DNA and the modified groups at both ends are NH2-(CH2)6-GGAAGACGTGAACGCAAGTGATCCTTTCTTCC-(C H2)6-SH, the concentration of hairpin DNA is 1 μmol / L, dried under a xenon lamp for 10 min, then 2 μL of 10 mol / L TCEP was added, dried under a xenon lamp for 20 min, and then Au@NiFeMOF solution dissolved in DMF was added dropwise, the concentration of Au@NiFeMOF solution was 2 mg / mL, the volume was 4 μL, dried under a xenon lamp for 40 min, 5 μL of 10 mol / L BSA solution was added, and finally dried under a xenon lamp for 30 min to obtain the modified electrode.
[0070] d. A three-electrode system was used, with the prepared modified electrode as the working electrode, the platinum electrode as the auxiliary electrode, and the silver-silver chloride electrode as the reference electrode. The above three electrodes were inserted into a PBS buffer solution containing a co-reactant (0.1 mol / L K2S2O8), and finally an electrochemical biosensor based on Au@NiFeMOFs composite material was constructed.
[0071] Through cyclic voltammetry, the scan rate is 100mV / s, and the cycle voltage is -2.5-0V, the working electrode obtains the cathode electrochemiluminescence behavior of the electrochemiluminescent material based on quantum dots, and at the same time, the electrochemiluminescence resonance energy transfer behavior between quantum dots and Au@NiFeMOF is caused. The electrochemiluminescence signal is tested by the BPCL ultra-weak luminescence instrument, and the intensity of the electrochemiluminescence signal is recorded. Figure 7 , 8 It can be seen that during the construction of the sensor, as the material is dripped onto the electrode, the impedance of the sensor gradually increases, proving that the sensor is successfully constructed.
[0072] Example 3
[0073] Electrochemical biosensor for detection of TLH gene of Vibrio parahaemolyticus:
[0074] According to the TLH sequence of Vibrio parahaemolyticus, a 50-base sequence was selected for simulation testing of actual samples. The base sequence is as follows:
[0075] GGTTGATGTCCAAACAAGGATCACTTGCGTTCACGAAACCGGTGCTCTTCT.
[0076] a. Use 0.01 mol / L PBS buffer solution with a pH of 7.4 to dilute the 10 μM TLH gene DNA solution to 100 pM-10 aM. The TLH gene DNA sequence was purchased from Shanghai Shenggong Biological Company.
[0077] b. Then, the target DNA solution to be tested was added dropwise to the modified electrode surface of the electrochemiluminescent biosensor, and the test was started after drying in a drying oven at 25° C. for 30 min.
[0078] Depend on Fig. 9 It can be seen that when the sensor is used to test the 20-base sequence of the target, the detection range is 100pm to 10am, with the lowest sensitivity being 10am.
[0079] Depend on Fig.10 It can be seen that the sensor detects the concentration of the target DNA. The curve fitted by the electrochemiluminescence intensity and the target DNA concentration has a regression equation of I=15347.9lgc-2109.6. After calculation, the minimum detection limit LOD of the sensor is 2.28am.
[0080] In summary, when the target object does not have the TLH gene, the electrochemiluminescence intensity is 3000-8000, and when the sensor detects the TLH gene, the intensity is 20000-200000, and the luminescence intensity is different at different concentrations. The higher the concentration of the target DNA detected by the sensor, the stronger the electrochemiluminescence intensity.
[0081] Although the above embodiments have been described in detail, they are only a part of the embodiments of the present invention, not all of them. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all belong to the protection scope of the present invention.
Claims
1. A method for preparing an Au@NiFeMOF composite material, characterized in that: The method uses NiFeMOF as a carrier, and uses a surface in-situ reduction method to uniformly load gold nanoparticles on the surface of NiFeMOF to synthesize an Au@NiFeMOF composite material.
2. The method according to claim 1, characterized in that: The preparation method of the NiFeMOF is as follows: a. Weigh potassium ferrocyanide, nickel chloride hexahydrate and sodium citrate; b. dissolving potassium ferrocyanide in water to obtain a potassium ferrocyanide solution; c. Then dissolving nickel chloride hexahydrate and sodium citrate in water to obtain a nickel source mixture; d. The potassium ferrocyanide solution and the nickel source mixed solution are mixed and dissolved by ultrasonication, and stirred until the solution becomes turbid and produces a large amount of precipitate, which is then washed and dried to obtain NiFeMOF.
3. The method according to claim 2, characterized in that: In the step a), the mass ratio of potassium ferrocyanide, nickel chloride hexahydrate and sodium citrate is 1:1-1.2:2-2.
2.
4. The method according to claim 2 or 3, characterized in that: In the step a), the mass ratio of potassium ferrocyanide, nickel chloride hexahydrate and sodium citrate is 1:1.09:2.
03.
5. The method according to claim 1, characterized in that: The Au@NiFeMOF composite material is loaded by the following method: a. Weigh NiFeMOF, polyvinyl pyrrolidone, potassium carbonate and sodium borohydride to prepare a 1% HAuCl4 solution; b. dissolving NiFeMOF and potassium carbonate in water to obtain NiFeMOF solution and potassium carbonate solution respectively; c. Add HAuCl4 solution to the NiFeMOF solution, stir evenly, then add polyvinyl pyrrolidone; then add potassium carbonate solution, and finally add sodium borohydride and stir evenly, centrifuge, wash and dry to obtain Au@NiFeMOF composite material.
6. The method according to claim 5, characterized in that: In the step a), the mass ratio of NiFeMOF, polyvinyl pyrrolidone, potassium carbonate and sodium borohydride is 1:0.8-1.2:1-1.5:1.7-2.5; the mass volume ratio of NiFeMOF to HAuCl4 solution is 7.5-9 mg / mL.
7. The method according to claim 5 or 6, characterized in that: In the step a), the mass ratio of NiFeMOF, polyvinyl pyrrolidone, potassium carbonate and sodium borohydride is 1:1:1.4:2.25; the mass volume ratio of NiFeMOF to HAuCl4 solution is 8.3 mg / mL.
8. Application of an Au@NiFeMOF composite material in the construction of electrochemiluminescence biosensor.
9. A method for constructing an electrochemiluminescent biosensor based on Au@NiFeMOFs composite material, characterized in that: The following steps are involved: a. dissolving Au@NiFeMOF in N,N-dimethylformamide to obtain Au@NiFeMOF solution; b. polishing the glassy carbon electrode, then cleaning it with deionized water, anhydrous ethanol and deionized water in turn, blowing the surface dry with N2, pre-treating and drying it for later use, and obtaining a pre-treated glassy carbon electrode; c. Drop 5 μL of fluorescent molybdenum disulfide quantum dot luminescent material on the surface of the pretreated glassy carbon electrode, dry it, then continue to drop 2 μL of 1-ethyl-(3-dimethylaminopropyl) carbodiimide and 2 μL of N-hydroxysuccinimide solution on the glassy carbon electrode, add 4 μL of hairpin DNA after drying, then add 2 μL of tri(2-carboxyethyl)phosphine, and then drop 4 μL of Au@NiFeMOF solution, add 5 μL of bovine serum albumin solution after drying, and finally dry it to obtain the modified electrode; d. A three-electrode system was used, with the prepared modified electrode as the working electrode, the platinum electrode as the auxiliary electrode, and the silver-silver chloride electrode as the reference electrode. The three electrodes were inserted into a PBS buffer solution containing a co-reactant, and the electrochemical luminescence signal was tested by a BPCL ultra-weak luminescence instrument. The intensity of the electrochemical luminescence signal was recorded, and finally an electrochemical biosensor based on the Au@NiFeMOFs composite material was constructed; In the step c), the base sequence of the hairpin DNA and the groups modified at both ends are as follows: NH2-(CH2)6-GGAAGACGTGAACGCAAGTGATCCTTTCTTC C-(CH2)6-SH.
10. Use of the electrochemiluminescent biosensor prepared by the method of claim 9 in detecting the TLH gene of Vibrio parahaemolyticus, characterized in that: The steps include: a. Dilute the 10 μM TLH gene DNA solution using PBS buffer solution to obtain a 100 pM to 10 aM DNA solution; wherein the base sequence of the TLH gene is as follows: GGTTGATGTCCAAACAAGGATCACTTGCGTTCACGAAAC CGTGCTCTTCT; b. Then the DNA solution is added dropwise to the modified electrode surface of the electrochemiluminescent biosensor and dried for testing; the concentration of the Vibrio parahaemolyticus TLH gene is detected.
